Bioconversion process for microbial treatment of palm oil mill effluent to produce citric acid - Jamal, Parveen; Alam, Md. Zahangir; Mohd Salleh, Mohammad Ramlan; Nadzir, Masrina M. (2006)
Oil palm is a very important asset in the Malaysian economy. It is estimated that for 1 tonne of crude palm oil produced, 5-7.5 tonnes of water is required and more than 50% of water end up as Palm Oil Mill Effluent (POME). The raw or partially treated POME has an extremely high content of degradable organic matter along with some unrecovered palm oil, which can cause severe pollution of waterways due to oxygen depletion and other related effects. On the other hand, efficient and effective methods of producing citric acid from different cheaper raw materials have been of great interest to many researchers, because of extensive use of this acid in various industrial processes. Demand for this particular metabolite is increasing day by day which requires a much more efficient fermentation process for higher product yield. When applied to appropriate mass balance, it is possible to predict the utilization of substrates and the yield of individual products. Fermentation media for citric acid biosynthesis should consist of substrates necessary for the growth of microorganism, primarily the carbon, nitrogen and phosphorus sources. In this line, POME is introduced as a cheaper raw material for citric acid production by microbial treatment with developed bioconversion process.